Morphological and Immunohistochemical Changes in Progressive Postmortem Autolysis of the Murine Brain - Francesca Parisi; Sara Degl’Innocenti; Çağla Aytaş; Andrea Pirone; Carlo Cantile (Animals)
In this time series study, the temporal sequences of postmortem changes in brains kept at different temperatures were investigated in different areas of mouse brains. Fixation of tissues kept at different storage temperatures (4 °C, 22 °C, 37 °C) was delayed for four time points (24, 120, 168, 336 h). Histological and immunohistochemical investigations were carried out to determine how postmortem autolysis may affect the cellular morphology and the expression of neural cell epitopes. Results showed that the autolytic changes started earlier in brains at 22 °C and 37 °C and in the grey matter compared to the white matter, with the cerebellum and hippocampus showing the earliest postmortem changes. The cellular antigens were differently affected by the autolytic process overtime: NeuN and Olig2 immunoreactivity was gradually lost at the nuclear site and diffused into the cytoplasm; increased background staining was observed with SMI-32; GFAP showed an increase in immunolabeling, whereas 2F11 immunoreactivity decreased. This study suggests that the morphological analysis and immunohistochemical investigation of the brain tissue could be satisfactorily applied to forensic cases, providing useful data for the estimation of the postmortem interval.